2013
DOI: 10.1136/heartjnl-2013-304073
|View full text |Cite
|
Sign up to set email alerts
|

Acute catecholamine cardiomyopathy in patients with phaeochromocytoma or functional paraganglioma

Abstract: PPGL may present as ACC in 11% of cases, excluding patients dying from undiagnosed tumours. Left ventricular dysfunction is usually reversible before surgery. PPGL should be suspected in patients with acute heart failure without evidence of valvular or coronary artery disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
89
1
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 23 publications
8
89
1
10
Order By: Relevance
“…Cardiovascular complications, such as hypertensive crisis and catecholamine-induced cardiomyopathy, are known to be the most frequent causes of life-threatening events in pheochromocytoma patients as summarized in a recently published review of the literature (12). Additionally, Giavarini et al (10) reported that 11% of pheochromocytoma patients present with acute catecholamineinduced cardiomyopathy. In agreement with these studies, four of our patients suffered from pheochromocytoma-induced Tako-Tsubo cardiomyopathy and presented with the sequence of hypertensive crisis followed by hypotensive shock.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiovascular complications, such as hypertensive crisis and catecholamine-induced cardiomyopathy, are known to be the most frequent causes of life-threatening events in pheochromocytoma patients as summarized in a recently published review of the literature (12). Additionally, Giavarini et al (10) reported that 11% of pheochromocytoma patients present with acute catecholamineinduced cardiomyopathy. In agreement with these studies, four of our patients suffered from pheochromocytoma-induced Tako-Tsubo cardiomyopathy and presented with the sequence of hypertensive crisis followed by hypotensive shock.…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…In 2013, Scholten et al (11) published a retrospective comprehensive study analyzing the perioperative management of pheochromocytoma crisis and recommended an elective adrenalectomy after cardiovascular stabilization and a-blockade; 137 patients from one United States center were included and zero mortality was reported. In the same year, Giavarini et al (10) presented a retrospective study including 140 patients with pheochromocytoma from a French center. They found catecholamine-induced cardiomyopathy in 11% of the patients and recommend screening for pheochromocytoma in patients with acute heart failure without evidence of valvular or coronary heart disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pulmonary edema is a rare clinical manifestation of pheochromocytoma, especially in patients with normal blood pressure or hypotension (Eschen et al, 2007;Giavarini et al, 2013). In most pheochromocytoma cases, pulmonary edema is cardiogenic and is caused by myocardial infarction, cardiomyopathy, and severe arrhythmias.…”
Section: Correspondencementioning
confidence: 99%
“…The incidence of TTS is reported to be only approximately 5% in clinical pheochromocytoma patients. 5 (d) The mortality associated with experimental TTS induced with high-dose catecholamine administration in small animals Is High-Dose Catecholamine Administration in Small Animals an Appropriate Model for Takotsubo Syndrome?…”
mentioning
confidence: 99%